Food and drug regulation in an era of globalized markets - Halabi, Sam F. (Academic Press, 2015)
Food and Drug Regulation in an Era of Globalized Markets provides a synthesized look at the pressures that are impacting today's markets, including trade liberalization, harmonization initiatives between governments, increased aid activities to low-and middle-income countries, and developing pharmaceutical sectors in China and India.